Operational Feasibility Assessment of Battery Electric Construction Equipment Based on In-Use Activity Data. Issue 9 (September 2021) - Un-Noor, Fuad; Scora, George; Wu, Guoyuan; Boriboonsomsin, Kanok; Perugu, Harikishan; Collier, Sonya; Yoon, Seungju
Despite the significant progress in on-road vehicle electrification, the majority of construction equipment types are still using conventional diesel engines. Though there has been a steady flow of studies in this field, not all equipment types have yet been evaluated. This paper contributes to filling that data gap by analyzing real-world second-by-second activity data from 17 off-road vehicles across six equipment types to investigate their electrification potential. The collected data are used to determine real-world power and torque demands—which are then used to select currently available electric motors suited for electrification of these types of equipment. Required battery sizes for battery electric operation are also calculated considering recorded energy demands, and battery sizes are standardized across equipment types for realistic implementation. The resulting battery electric systems are simulated to determine their effectiveness in fulfilling real-world activity demands. The results show that four of the six types can be electrified to a significant extent using battery electric powertrains with a single-motor set-up, while the remaining two types are more suitable for hybridization because of their high energy needs.